Use of some catalysts in radiolytical split of water [Articol] - Cecal, Alexandru; Paraschivescu, Andrei; Gulea, Aurelian; Palamaru, Mircea; Iordan, Alexandra; Popa, Karin; Craus, Mihai (My University, 2002)
The present paper deals with the study of catalyzed water radiolysis under the influence of γ-rays emitted by a 60Co source (Λ = 3 × 104 Ci) with a dose rate of 8.3 kGy/h, for hydrogen production. Thirty-one solid inorganic compounds, insoluble in water, were tested as catalysts. They belong to: coordination compounds of some metallic ions with organic ligands based on salycilaldehyde or naphthalenaldehyde derivatives, mixed oxides, RhCl3 supported on a Al2O 3 layer and bimetallic compounds with EDTA ligand. The released hydrogen quantity, determined by mass spectrometry, was approximately 7-35 times greater than the one produced by simple radiolysis of water, in the absence of catalysts.
Keywords: Engineering controlled terms Aromatic hydrocarbons; derivatives; Gamma rays; irradiation; Mass spectrometry; Nuclear reactors; Radiolysis; Water Engineering uncontrolled terms Bimetallic compounds; Ionizing nuclear radiations; Irradiation distance; Solid inorganic compounds Engineering main heading Catalysts